Dataset for pLAST: a tool for rapid comparison and classification of bacterial plasmid sequences - Stanislaw Dunin-Horkawicz (22550585) (2025)
This repository contains trained pLAST eggNOG- and MMseqs2-based models together with accessory files (metadata and precomputed embeddings). For a detailed description of the file structure and usage, please refer to the included README.md file.